Pharmacological treatment of idiopathic pulmonary fibrosis: current approaches, unsolved issues, and future perspectives - Kreuter, Michael; Bonella, Francesco; Wijsenbeek, Marlies; Maher, Toby M.; Spagnolo, Paolo (BioMed research international, 2015)
Idiopathic pulmonary fibrosis (IPF) is a devastating condition with a 5-year survival of approximately 20%. The disease primarily occurs in elderly patients. IPF is a highly heterogeneous disorder with a clinical course that varies from prolonged periods of stability to episodes of rapid deterioration. In the last decade, improved understanding of disease mechanisms along with a more precise disease definition has allowed the design and completion of a number of high-quality clinical trials. Yet, until recently, IPF was essentially an untreatable disease. Finally, pirfenidone and nintedanib, two compounds with antifibrotic properties, have consistently proven effective in reducing functional decline and disease progression in IPF. This is a major breakthrough for patients and physicians alike, but there is still a long way to go. In fact, neither pirfenidone nor nintedanib is a cure for IPF, and most patients continue to progress despite treatment. As such, comprehensive care of patients with IPF, including management of comorbidities/complications and physical debility and timely referral for palliative care or, in a small number of highly selected patients, lung transplantation, remains essential. Several agents with high potential are currently being tested and many more are ready to be evaluated in clinical trials.
Gesehen am 29.07.2020